PENINGKATAN KESADARAN MASYARAKAT TERHADAP PENGGUNAAN OBAT YANG AMAN DAN RASIONAL MELALUI EDUKASI DAGUSIBU DAN GEMA CERMAT DI RPTRA CHIBI - JuliaTotong; Albert Sanders (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Irrational medication use remains a public health issue in Indonesia. Low health literacy often leads the public to use medications without regard for indications, dosage, duration of use, or storage guidelines. Such practices increase the risk of adverse drug reactions, drug interactions, antibiotic resistance, and therapeutic failure. This community service activity aimed to enhance public knowledge and awareness regarding safe and rational medication use through education based on the DAGUSIBU program and the *Gerakan Masyarakat Cerdas Menggunakan Obat* (GeMa CerMat—Community Movement for Smart Medication Use). The methods employed included interactive sessions, group discussions, demonstrations of proper medication use, distribution of educational materials, and evaluation using pre-tests and post-tests. The activity involved 10 participants from the general public. Evaluation results showed an increase in the average knowledge score from 7,1 to 9,5, representing at 25% improvement. Furthermore, there was increased understanding regarding medication classification, prudent antibiotic use, medication storage, and the disposal of expired medicines. Participants also demonstrated a more positive attitude toward using medications in accordance with healthcare professionals' recommendations. Education based on DAGUSIBU and GeMa CerMat proved effective in improving public health literacy, thereby supporting safe and rational medication use.